1998
DOI: 10.1063/1.873128
|View full text |Cite
|
Sign up to set email alerts
|

Chaotic oscillations enhanced by magnetosonic waves in plasma-filled traveling-wave tubes

Abstract: A theory of plasma-filled traveling-wave tubes (TWTs) is developed in which the effect of magnetosonic waves excited in plasma by the operating wave is taken into account. These waves are excited by the ponderomotive force caused by the radial inhomogeneity of the axial component of the electric field of the operating wave. In the simplest case considered in the paper, this effect leads to an additional reactive nonlinearity in the wave envelope equation. This leads to a shrinkage of the region of stable oscil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 12 publications
1
11
0
1
Order By: Relevance
“…Subsequent increasing of either the amount of feedback or the TWT gain result in a period-doubling transition to chaos. 10,15,16,24,26 For a TWT with a narrowband filter in the feedback leg, therefore, the role of the phase nonlinearity becomes subsidiary and basically leads to a nonlinear frequency shift leading to more uniform spectrum in the chaotic regime. It has been observed, for example, that in a nonstationary regime with strong amplitude modulation, the effect of the AM/PM nonlinearity causes "wobbling" of the basic frequencies and thus broadening of discrete spectral lines.…”
Section: -10mentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequent increasing of either the amount of feedback or the TWT gain result in a period-doubling transition to chaos. 10,15,16,24,26 For a TWT with a narrowband filter in the feedback leg, therefore, the role of the phase nonlinearity becomes subsidiary and basically leads to a nonlinear frequency shift leading to more uniform spectrum in the chaotic regime. It has been observed, for example, that in a nonstationary regime with strong amplitude modulation, the effect of the AM/PM nonlinearity causes "wobbling" of the basic frequencies and thus broadening of discrete spectral lines.…”
Section: -10mentioning
confidence: 99%
“…In this case, the self-modulation is caused by the presence of a steep negative slope in the AM/AM curve. 10,15,16 The qualitative explanation to the amplitude mechanism is as follows. Consider the stationary regime when the TWT gain is close to or equal to the feedback attenuation.…”
Section: -10mentioning
confidence: 99%
See 1 more Smart Citation
“…Ponderomotive effects in plasma-filled microwave tubes were analyzed in [63,64], where it was shown that these effects may lead to various nonstationary phenomena. Recall that the ponderomotive force f p is the force that acts on electrons moving in a slightly inhomogeneous electromagnetic field.…”
Section: Ponderomotive Effectsmentioning
confidence: 99%
“…In the presence of plasma waves the system may exhibit some mode hopping effects, e.g., from a mode with two axial variations to a mode with three variations. In [64], a plasma-filled TWT was studied. It considered the case of a plasma column of small radius at finite magnetic fields when the ponderomotive force caused by the radial inhomogeneity of |£*| 2 …”
Section: Note Thementioning
confidence: 99%